PENERAPAN SUB POKOK FUNGSI PADA MATEMATIKA EKONOMI DAN BISNIS TERHADAP FUNGSI LINIER - Listiyowati, Emilia Indah; Maisaro, Icha; Azril Firdaus, Mochammad; Sulkhi Arofi, Muhammad; Ayu Zaskia, Nurdiyah; Mariyam, Rena Firda (JIEM : Journal Of International Entrepreneurship And Management, 2024)
This article discusses the concept of linear functions, which is one of the basic topics in mathematics and is of great importance in various disciplines, including physics, economics, and computer science. The main focus of this article is to explain the properties of linear functions, including their straight-line graphs, as well as their applications. In addition, the article also discusses ways to determine the slope of the line, which provides important information about the relationship between two variables. The method of analysis is descriptive research with a qualitative approach. The results show that linear functions are used to represent simple relationships between two variables, such as in economics for the relationship between price and demand, and in physics to describe the relationship between constant velocity and distance. A linear function is defined as a function that has the general form (f(x) = (ax + b), where (a) and (b) are constants, and (x) is the independent variable.